ANALISIS MOTIVASI KONSUMEN DALAM PROSES KEPUTUSAN PEMBELIAN BUSANA SYAR’I TERHADAP MAHASISWA MANAJEMEN 2016 FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS MUHAMMADIYAH MAKASSAR - Agussalim Harrang; Sulaeman Masnan; Mardilah Mardilah (Jurnal Ilmu Manajemen Profitability, 2020)
This study aims to determine and analyze the motivation of consumers in the process of shariah clothing purchase decisions in management students of the 2016 Faculty of Economics and Business, University of Muhammadiyah Makassar. The type of research used is qualitative, using interview techniques, observation and documentation. Based on the results of research from the analysis that has been carried out, it can be concluded that several things can be motivated by Management Students 2016 Faculty of Economics and Business on the decision to purchase sharia clothing, namely; Introducing needs, information seeking, alternative evaluations, purchasing decisions, and post-purchase behavior.